Paradiplomacy for Cyber Resilience in Jakarta: Between Progress, Loopholes, and the Struggle to Secure the Digital City - Rino, Meyer Rafael; Zaki Syaiful Hunafa (Journal of Paradiplomacy and City Networks, 2026)
Rapid digital transformation in big cities like Jakarta has increased their vulnerability to increasingly complex and cross-border cyberattacks. This issue makes digital public security a strategic agenda in local governance. The increasing number of attacks on public infrastructure, government services, and the private sector shows that strengthening cyber resilience cannot only rely on policies from the central government. In this context, the role of paradiplomacy and subnational actors in foreign relations is an important approach to improving local cybersecurity capacity. This study analyzes how Jakarta, as one of the big cities in Indonesia, responds to cyber threats through paradiplomacy mechanisms. The focus of this study is on institutional adjustments, cross-border collaboration, and the role of local and transnational actors in addressing cybersecurity challenges. This study aims to contribute to paradiplomacy in the context of cybersecurity by using a descriptive qualitative method that analyzes documents, digital reports, and policies from local governments. In addition, this study also offers practical recommendations for public security policies based on inclusive and sustainable multi-level governance to ensure better cyber resilience in the era of digital transformation. It is hoped that the findings from this study can provide input for policymakers who are more effective in dealing with cyber threats at the local and international levels in a more resilient and inclusive manner in the era of ever-growing digital transformation.